Development of a thermally processed suman sa ibus - Pacquing, Debby Felipe; Galvez, Flor Crisanta F. (1996.)
Heat penetration studies on canned Suman sa Ibus were conducted. The amount of water that would be added in the product in cans was determined in preliminary studies. Best results were obtained when 110 milliliters water was used in the processing of the product in 307x409 C Enamel cans at 250°F. Heat penetration tests found the lethality process for the product to be 18.30 minutes.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Snack foods